Intravenous administration of dexmedetomidine and quality of recovery after elective surgery in adult patients: A meta-analysis of randomized controlled trials - Miao, Mengrong; Xu, Yuehua; Li, Bing; Chang, Enqiang; Zhang, Liyuan; Zhang, Jiaqiang (Journal of clinical anesthesia, 2020)
To evaluate the efficacy and safety of pre- and perioperative intravenous administration of dexmedetomidine for enhancing quality of recovery (as measured by 40-item quality of recovery questionnaire (QoR-40), ranged from 40 to 200) after surgery. Meta-analysis. Adult patients undergoing elective surgery. Intravenous administration of dexmedetomidine during pre- and perioperative period. The primary outcome was quality of recovery after surgery. The secondary outcome was the incidence of dexmedetomidine-related adverse events. Moderate to low quality evidence suggested that dexmedetomidine (DEX) increased the quality of recovery after surgery (WMD, weighted mean difference 15.71, 95% CI, confidence interval 0.43 to 31.00; 428 participants; 5 RCTs; low quality evidence), decreased the incidence of postoperative nauseas or vomiting (RR, risk ratio 0.60, 95% CI 0.44 to 0.83; 404 participants; 6 RCTs; moderate quality evidence; RR 0.32, 95% CI 0.19 to 0.55; 356 participants; 5 RCTs; moderate quality evidence) without increased risk of bradycardia (RR: 1.78, 95% CI 0.78 to 4.02; 275 participants; 4 RCTs; moderate quality evidence), dizziness (RR 0.78, 95% CI 0.31 to 2.00; 183 participants; 3 RCTs; moderate quality evidence), pruritus (RR 1.32, 95% CI 0.39 to 4.44; 186 participants; 3 RCTs; moderate quality evidence), hypotension requiring an intervention (RR: 1.48, 95% CI, 0.68 to 3.23; 254 participants; 3 RCTs; moderate quality evidence) and longer length of hospital stay (WMD: −0.75 days, 95% CI −1.95 to 0.44; 246 participants; 3 RCTs; low quality evidence) in early postoperative period. Dexmedetomidine as an anesthetic adjuvant to general anesthesia was associated with an enhanced quality of recovery (15.71; far more than a clinically significant improvement of 6.3) without increased risk of adverse events in the early postoperative period (moderate to low quality evidence). Further large sample and high quality RCTs are needed to confirm the current findings. •Dexmedetomidine as an anesthetic adjuvant to general anesthesia was related to a better quality of recovery after surgery•Intravenous administration of dexmedetomidine may not increase risk of adverse events in the early postoperative period•This study investigating the efficacy and safety of dexmedetomidine for enhancing quality of recovery after surgery.